Survey of the English Language Needs of the Senior Students of Physical and Biomedical Sciences - Rozgienė, Inga; Trečiokaitė, Albina (Verbum, 2011)
The new generation of students with a different mindset and completely changed possibilities and opportunities offered by the rapid development of IT in the changing globalized world need more specific English language skills at different stages of their studies. Most of the programmes at Vilnius University include English for Specific Purposes during the first 2–4 semesters of studies, however, specific future speciality-related subjects are usually studied in the later years; senior students become involved in academic research and communication, and it is then that the need for certain English language skills arises. In order to meet the students’ new language needs, teachers of the Department of English for Physical and Biomedical Sciences of the Institute of Foreign Languages of Vilnius University carried out a survey at the Faculties of Chemistry, Mathematics and Informatics, Medicine, Natural Sciences, and Physics. The study was conducted by means of an anonymous questionnaire covering students of senior years (those who have already completed the English language course and passed the final examination) as the target group. The aim of this paper is to present the results of the above multi-purpose survey: to obtain a retrospective feedback on the ESP taught, identify the dynamics in the students’ needs at higher levels of tuition as well as gain some insights into the possible gaps/lacks in the present scheme of the delivery of ESP which may have some implications for improvement / modifications in the further process of teaching ESP, thus contributing to the refinement of the quality of the course.